The beguiled (2017) [videorecording (DVD)] - Coppola, Sofia, 1971-; Farrell, Colin, 1976-; Kidman, Nicole, 1967-; Dunst, Kirsten, 1982-; Fanning, Elle, 1998-; Cullinan, Thomas (Universal Pictures Home Entertainment, 2017)
At a girls' school in Virginia during the Civil War, where the young women have been sheltered from the outside world, a wounded Union soldier is taken in. Soon, the house is taken over with sexual tensions, rivalries, and an unexpected turn of events.